2020
DOI: 10.1111/1467-8268.12424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of farm credit access on agricultural commercialization in Ghana: Empirical evidence from the northern Savannah ecological zone

Abstract: The purpose of this paper is to investigate how farmers' access to credit affects agricultural commercialization in the northern Savannah ecological zone of Ghana. The study uses data from the Ghana Feed the Future baseline survey involving a total sample of 2,962 farm households. The study employs endogenous switching regression for ordered outcomes to account for endogeneity and self-selection bias in the decision to access credit. The results from the estimations revealed that education, age, nonfarm busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 36 publications
(39 reference statements)
8
31
1
2
Order By: Relevance
“…On this basis, production of market‐oriented crops (such as horticultural crops), as well as targeting high value markets, is critical to poverty reduction of youth while at the same time improving the youth unemployment situation in rural areas. Thus, numerous studies (e.g., Abdul‐Rahaman & Abdulai, 2020; Fan & Garcia, 2018; Sekyi et al, 2020) provide critical factors that motivate smallholder participation in markets.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…On this basis, production of market‐oriented crops (such as horticultural crops), as well as targeting high value markets, is critical to poverty reduction of youth while at the same time improving the youth unemployment situation in rural areas. Thus, numerous studies (e.g., Abdul‐Rahaman & Abdulai, 2020; Fan & Garcia, 2018; Sekyi et al, 2020) provide critical factors that motivate smallholder participation in markets.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In terms of empirical studies on agricultural productivity, the literature has concentrated on the relationship between farm size and productivity (Sekyi et al, 2017) and has generally found that small farms are more productive than large farms (see Barrett, Bellemare, & Hou, 2010; Kimhi, 2003; Larson, Otsuka, Matsumoto, & Kilic, 2012; Mazumdar, 1965). For example, the studies of Kimhi (2003) and Larson et al (2012) showed that productivity responds negatively to increases in farm sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Such credit market failures are observed to be Alhassan et al Access to credit, productivity And mArket pArticipAtion 227 occasioned by adverse selection and moral hazards (see, Akerlof, 1970;Stiglitz & Weiss, 1981), which in turn impose the need for credit institutions to screen credit applicants. Sekyi, Abu, and Nkegbe (2017) note that the screening and sorting behaviours of financial institutions are the underlying explanation for the dichotomous response from credit application: either an applicant secures the credit or otherwise. Therefore, if a set of farmers apply for credit, credit institutions screen the applications on the basis of personal, household, institutional factors among others, and determine those that qualify for credit.…”
Section: Introductionmentioning
confidence: 99%
“…This study used a maximum likelihood method to jointly estimate the marginal effects associated with the three-step decisions made by mango farmers. Sekyi et al. (2017) argue that a simultaneous estimation of multiple equations gives efficient estimates and thus allows for the testing of the correlations between the error terms.…”
Section: Methodsmentioning
confidence: 99%